2019
DOI: 10.24136/oc.2019.008
|View full text |Cite
|
Sign up to set email alerts
|

Limitations in availability of food in Ukraine as a result of loss and waste

Abstract: Research background: The commitment to increasing the volume of agricultural production remains the main strategy for food supply in Ukraine. In fact, such an approach does not solve the problem of the limitation of food’s physical availability. It works quite the opposite way, as there is a guaranteed food loss and waste, worsened environmental situation and decreased level of economic availability of food. Purpose of the article: According to the results of the empirical study, the volume of food short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
1
13
0
1
Order By: Relevance
“…At the same time, the comparison of these indicators reflects the economic availability of products and the degree of satisfaction of human needs in the nutrition. Another important criterion for the sustainability of the food system is the physical availability of food in a certain territory and its storage in places that provide the required level of product quality (Kotykova, 2019).…”
Section: Management Theory and Studies For Rural Business And Infrastmentioning
confidence: 99%
“…At the same time, the comparison of these indicators reflects the economic availability of products and the degree of satisfaction of human needs in the nutrition. Another important criterion for the sustainability of the food system is the physical availability of food in a certain territory and its storage in places that provide the required level of product quality (Kotykova, 2019).…”
Section: Management Theory and Studies For Rural Business And Infrastmentioning
confidence: 99%
“…Governments, industry, agriculture and the economy as a whole (macro-environment) (Virglerova et al, 2020). Food security is the responsibility of every state, it is part of every state's security and global security (Kotykova & Babych, 2019). Swinnen (2015) concluded that the CAP "increased flexibility in the implementation of the policies and the allocation of funds, and relatively minor changes in environmental and market regulations."…”
Section: Introductionmentioning
confidence: 99%
“…Low-and middle-income developing countries rich in natural resources often face the problem of low consumption of agricultural products due to low production diversification and the abundance of imported or cheaper substitutes in the domestic market that are in high demand. Most often this can be explained by the desire of poor developing countries to integrate into the global trade in order to promote their national products (Kotykova and Babych, 2019). It is not always possible to fully realize export ambitions, since to enter, for example, European or North American markets, it is necessary to break through significant barriers related to high quality, compliance with environmental regulations and standards and food safety (Szczepaniak, 2018).…”
Section: Introductionmentioning
confidence: 99%